Dampak Budaya Kerja Aparatur terhadap Kualitas Pelayanan pada Program Plase Care Papa di Kabupaten Padang Pariaman - Bella Kharisma Putri; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study aims to determine the impact of civil service work culture on service quality in the Please Care Papa program in Padang Pariaman Regency. Please Care Papa is an online service that is useful forhelp identify the needs of the poor based on profiles in an integrated database linking the poor to social protection and poverty alleviation programs carried out by the Central Government, Provincial Governments and District Governments according to the needs of the poor. The research method used is descriptive qualitative. The selection of informants was used by purposive sampling technique. In collecting data, the writer uses interview, observation and documentation techniques. The results of the research that have been carried out can be concluded that not all services can run with the online system seen from the target users of the Please Care Papa website are the poor who have limitations and the ability to technology. The lack of socialization provided to the community is also an obstacle in implementing this online service so that there are still many people who do not know about the online services provided by the Office for Women's Empowerment and Child Protection through the Please Care Papa website.